Acitretin Treatment for Lipoid Proteinosis - Özgür Gündüz; Neriman Şahiner; Pınar Atasoy; Çağrı Şenyücel (Case Reports in Dermatological Medicine)
Lipoid proteinosis (LP) is a rare, autosomal-recessive disease characterized by the hoarseness and widespread cutaneous scarring, more prominent on sun-exposed areas. Yellow-white plaques can be seen on oral mucosa and on the skin among depressed scars. Histological evaluation of the affected sites shows accumulation of hyaline-like material in dermis and disruption of basement membrane. Although LP is compatible with normal life expectancy, involvement of upper respiratory tract may endanger patient's life, especially in the case of a respiratory tract infection. Involvement of central nervous system has also been reported, but its clinical importance is obscure. Due to the rarity of LP, a definite therapeutical approach is not established. In this paper we describe a 21-year-old LP patient who was treated with acitretin for six months. Although the outcome with cutaneous lesions was not satisfactory, her hoarseness was significantly improved.